The Fun Formula : How Curiosity, Risk-Taking, and Serendipity Can Revolutionize How You Work - Comm, Joel (Nashville, Tennessee : Nelson Books, an imprint of Thomas Nelson, 2018)
"Find more success in work and in life than you ever dreamed possible--by pursuing fun. The demands of work and the breakneck pace of technological change wear heavily on all of us, whether we are employees at a large company, solo workers in the gig economy, or entrepreneurs launching a new venture. the 'hustle and grind' lifestyle that we've been told is essential to success actually leads to physical ailments, emotional burnout, and a darkness in the soul. But Joel Comm has found a better way" --
Includes bibliographical references (pages 199-202).
Keywords: Success in business; Success; Job satisfaction; Quality of work life; Quality of life